2022
DOI: 10.1042/bsr20220194
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing of Tunisian Leigh syndrome patients reveals novel variations: impact for diagnosis and treatment

Abstract: Mitochondrial cytopathies, among which the Leigh syndrome (LS), are caused by variants either in the mitochondrial or the nuclear genome, affecting the oxidative phosphorylation process. The aim of this study consisted in defining the molecular diagnosis of a group of Tunisian patients with LS. Six children, belonging to five Tunisian families, with clinical and imaging presentations suggestive of LS were recruited. Whole mitochondrial DNA and targeted next generation sequencing of a panel of 281 nuclear genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Through this study, we emphasize the relevance and significance of early genetic testing in accurately confirming the clinical diagnosis of mitochondrial diseases. This approach ensures improved healthcare management for patients and allows for timely intervention, particularly in the cases where effective treatments are available (Hechmi et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Through this study, we emphasize the relevance and significance of early genetic testing in accurately confirming the clinical diagnosis of mitochondrial diseases. This approach ensures improved healthcare management for patients and allows for timely intervention, particularly in the cases where effective treatments are available (Hechmi et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Today, the spectrum of SLC19A3 variants has expanded to neurologic mitochondrial syndromes, with the most common being LS (Gerards et al, 2013;Ortigoza-Escobar et al, 2014;Ortigoza-Escobar et al, 2016). The p.T422A variant is a recurrent pathogenic mutation in the Arab region, which was identi ed with a founder effect in the Saudi Arabian population for BTRBGD (Alfadhel et al, 2013) and was recently reported in a Tunisian LS patient (Hechmi et al, 2022). Supplementation of thiamine and biotin can be effective in treating patients harboring de ciency in thiamine transporter genes such as SLC19A3 and SLC25A19, since it can increase intracellular thiamine levels.…”
Section: Discussionmentioning
confidence: 99%